Imprensa e instrução na Parahyba do Norte: cultura educacional e culturas políticas nos anos de 1880. - Souza, Thiago Oliveira de (2013)
In this dissertation we discussed the form that the education/instruction was considered in the press of Paraíba in the nineteenth century, point out the aspects of the educational and political cultures in the Province of Parahyba do Norte. The documental corpus used as support for this work was the editorials of the newspapers of Paraiba, available in the Historical and Geographicof Paraiba Institute and in Digital Hemeroteca of the National Library. Also used, in a smaller proportion, were the Province Presidents Reports in the decade of 1880. The range proposed for the elaboration of the present work is the years started from 1881 until 1889. Due the characteristics of our sources this was the moment in that was possible to delimit an educational debate among conservator and liberal parties. Our goal was to understand the educational culture spread through the texts of the political agents and journalists of Paraíba. We observed the speeches of conservatives and liberates, pointing out the divergences and similarities between them. Taking into account the accessibility to the impressed material of the epoch, we can say that the press of the nineteenth century had a considerable broadcast, being responsible for the popularization of ideas and speeches, besides, probably, it was one of the only channel of communication of this period. In the pages of the nineteenth century press was presented the everyday of the society, in special the themes related to the politics and the disputes of the parties. Among the considered themes, the instruction was the protagonist in several moments, being a frequent subject and source of intense debates. This work is related to the Program of Masters degree in History of the Federal University of Paraíba, in the branch of History Teaching and Historical Known.